Carriage of stx2a Differentiates Clinical and Bovine-Biased Strains of Escherichia coli O157 - Shringi, Smriti; Schmidt, Carrie; Katherine, Kaya; Brayton, Kelly A.; Hancock, Dale D.; Besser, Thomas E. (PloS one, 2012)
Shiga toxin (Stx) are cardinal virulence factors of enterohemorrhagic E. coli O157:H7 (EHEC O157). The gene content and genomic insertion sites of Stx-associated bacteriophages differentiate clinical genotypes of EHEC O157 (CG, typical of clinical isolates) from bovine-biased genotypes (BBG, rarely identified among clinical isolates). This project was designed to identify bacteriophage-mediated differences that may affect the virulence of CG and BBG. Stx-associated bacteriophage differences were identified by whole genome optical scans and characterized among >400 EHEC O157 clinical and cattle isolates by PCR. Optical restriction maps of BBG strains consistently differed from those of CG strains only in the chromosomal insertion sites of Stx2-associated bacteriophages. Multiplex PCRs (stx1, stx2a, and stx2c as well as Stx-associated bacteriophage-chromosomal insertion site junctions) revealed four CG and three BBG that accounted for >90% of isolates. All BBG contained stx2c and Stx2c-associated bacteriophage-sbcB junctions. All CG contained stx2a and Stx2a-associated bacteriophage junctions in wrbA or argW. Presence or absence of stx2a (or another product encoded by the Stx2a-associated bacteriophage) is a parsimonious explanation for differential virulence of BBG and CG, as reflected in the distributions of these genotypes in humans and in the cattle reservoir.